Studi tentang korban bullying pada Siswa kelas IX MTs Raudhatul Ulum Pematang Rambai Desa Kuala Mandor A tahun 2023 - A’yun, Qurrotul; Yuline, Yuline; Putri, Amallia (Academy of Education Journal, 2024)
This study aims to determine students who are victims of bullying. This study uses qualitative descriptive data sources in this study are 2 students of class IX MTS Raudahtul Ulum Pematang Rambai Kuala Mandor A. The technique used is the source triangulation technique, namely the subject, classmates, class teachers and counseling teachers. The method used is phenomemology with data collection techniques of interviews, observation, and documentation. Data analysis uses an interactive model consisting of data reduction, data presentation and conclusion drawing stages. The results showed the symptoms experienced. subject one physically bruised, sick because of the truth, skipping school, social changes, emotions are not stable. the factors that cause being a victim of bullying are small physique, geeky, difficult to get along, low self-confidence, awkwardness, different accents, less good at reading and writing, and stuttering. the impact experienced by victims of bullying feels uncomfortable, low self-esteem, poor social adjustment, fear of social difficulties, decreased academic achievement. subject two, experiencing bruises, often alone, disturbed lifestyle. The causative factors such as being weak-bodied, difficult to get along, shy, annoying, the impact that occurs on the victim feels unsafe at school. lazy to go to school, changes in social, solitary, difficult to concentrate, shy, unstable emotions. the role of counseling guidance for students who are victims of bullying is to provide co-services.